Vasopressin differentially modulates the excitability of rat olfactory bulb neuron subtypes - Suyama, Hajime; Bianchini, Gaia; Lukas, Michael (Frontiers in Neural Circuits, 2024)
Vasopressin (VP) plays a crucial role in social memory even at the level of the olfactory bulb (OB), where OB VP cells are activated during social interactions. However, it remains unclear how VP modulates olfactory processing to enable enhanced discrimination of very similar odors, e.g., rat body odors. Thus far, it has been shown that VP reduces firing rates in mitral cells (MCs) during odor presentation in vivo and decreases the amplitudes of olfactory nerve-evoked excitatory postsynaptic potentials (ON-evoked EPSPs) in external tufted cells in vitro. We performed whole-cell patch-clamp recordings and population Ca2+ imaging on acute rat OB slices. We recorded ON-evoked EPSPs as well as spontaneous inhibitory postsynaptic currents (IPSCs) from two types of projection neurons: middle tufted cells (mTCs) and MCs. VP bath application reduced the amplitudes of ON-evoked EPSPs and the frequencies of spontaneous IPSCs in mTCs but did not change those in MCs. Therefore, we analyzed ON-evoked EPSPs in inhibitory interneurons, i.e., periglomerular cells (PGCs) and granule cells (GCs), to search for the origin of increased inhibition in mTCs. However, VP did not increase the amplitudes of evoked EPSPs in either type of interneurons. We next performed two-photon population Ca2+ imaging in the glomerular layer and the superficial GC layer of responses to stronger ON stimulation than during patch-clamp experiments that should evoke action potentials in the measured cells. We observed that VP application increased ON-evoked Ca2+ influx in juxtaglomerular cells and GC somata. Thus, our findings indicate inhibition by VP on projection neurons via strong ON input-mediated inhibitory interneuron activity. This neural modulation could improve representation of odors, hence, better discriminability of similar odors, e.g., conspecific body odors.